2000
DOI: 10.1136/bjsm.34.6.456
|View full text |Cite
|
Sign up to set email alerts
|

Ocular sports injuries: the current picture

Abstract: Objectives-To determine the recent incidence of eye injury due to sport in Scotland, identify any trend, and establish which sports are responsible for most injury? The type of injury and final visual outcome is also evaluated. Methods-A prospective observational study of ocular injuries sustained during sport was performed over a one year period. Only patients requiring hospital admission were included. Data were collected on a standardised proforma and entered into a central database. Patients were followed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 12 publications
4
28
0
1
Order By: Relevance
“…The medical fraternity also have a very important role to play in educating the coaches, parents, and children and thus put an end to unnecessary blindness and vision loss from sports related ocular injuries, ensuring a lifetime of healthy vision. 1,11 Most common mechanisms of eye injuries…”
Section: Introductionmentioning
confidence: 99%
“…The medical fraternity also have a very important role to play in educating the coaches, parents, and children and thus put an end to unnecessary blindness and vision loss from sports related ocular injuries, ensuring a lifetime of healthy vision. 1,11 Most common mechanisms of eye injuries…”
Section: Introductionmentioning
confidence: 99%
“…With such activities, sport-related eye injuries have become a concern around the world as the incidence has been steadily increasing [2] [8]. These injuries can be fatal for sight, being responsible for up to one-third of all cases of blindness in the United States [9].…”
Section: Discussionmentioning
confidence: 99%
“…Canavan et al in 1980 reported the incidence of sport eye injures of 4.1% [4], and Jones, in 1988, showed the increase of percentage to 25.1% [5], while in MacEwen's paper, 1989, the proportion of sport eye injures was 42.2% [6]. At the beginning of 21st century such percentage was decreased, and therefore, Barr et al, in their study in 2000, reported the sport eye injury incidence of 12.5% [2], and in 2007 study by Len et al, such percent was 11% [7]. This paper analyzes the incidence, nature of injury and functional sequelae of sport injuries in Serbia in the first decade of our century.…”
Section: Introductionmentioning
confidence: 98%
“…In the past decade, the incidence of sport eye injuries tended to have increasing growth [1,2]. Garrow, in 1923, reported that the sport eye injuries accounted only for 0.7% of all patients admitted for treatment of their eye injures in the Glasgow Royal Infirmary [3].…”
Section: Introductionmentioning
confidence: 99%